Identification and characteristics of differentially expressed genes under UV-B stress in Gossypium hirsutum - Song, Xiaolin; Zhu, Yingjie; Bao, Ying (Frontiers in Plant Science, 2025)
ObjectiveThis study aimed to screen the differentially expressed genes (DEGs) of Gossypium hirsutum under UV-B stress and identify the significant pathways based on gene enrichment analysis results.MethodsIn this study, the allotetraploid crop G. hirsutum was used to examine changes in various physiological indexes under UV-B stress, and screened out all DEGs under UV-B stress (16 kJ m-2 d-1) based on six leaf transcriptomes. The main enrichment pathways of DEGs were analyzed according to gene annotation. Finally, we predicted the regulatory genes of phenylpropanoid pathway under UV-B stress by co-expression network analysis, and selected GhMYB4 for verification.ResultsGene annotation analysis revealed that DEGs were predominantly enriched in pathways related to photosynthesis and secondary metabolism. Further analysis revealed that UV-B stress impaired photosynthesis mainly by damaging photosystem II (PSII) and inhibiting electron transport, whereas G. hirsutum responded to UV-B stress by synthesizing secondary metabolites such as anthocyanins and lignin. We selected the regulatory genes GhMYB4 for verification. It was found to be an anthocyanin negative regulator in response to UV-B stress.ConclusionsUV-B stress impaired photosynthesis mainly by damaging photosystem II (PSII) and inhibiting electron transport, whereas G. hirsutum responded to UV-B stress by synthesizing secondary metabolites such as anthocyanins and lignin.